1993
DOI: 10.1016/s0934-8840(11)80851-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Virulence Factors of Legionella pneumophila

Abstract: SummaryLegionella pneumophila, the causative agent of Legionnaires' disease is a facultative intracellular bacterium, which in the course of human infection multiplies in lung macrophages predominantly manifesting as pneumonia. The natural habitat of Legionella is found in sweet water reservoirs and man-made water systems. Virulent L. pneumophila spontaneously convert to an avirulent status at a high frequency. Genetic approaches have led to the identification of various L. pneumophila genes. The mip (macropha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…We have demonstrated that use of the STM method identified a broad range of potential L. pneumophila virulence genes, far in excess of those discovered to date by using screening of transposon mutants in M cell lines or targeted mutagenesis (6)(7)(8)(27)(28)(29)(30). The key to obtaining the broad spectrum of mutants appears to be the use of an animal pneumonia model for screening the mutants, rather than M assays.…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated that use of the STM method identified a broad range of potential L. pneumophila virulence genes, far in excess of those discovered to date by using screening of transposon mutants in M cell lines or targeted mutagenesis (6)(7)(8)(27)(28)(29)(30). The key to obtaining the broad spectrum of mutants appears to be the use of an animal pneumonia model for screening the mutants, rather than M assays.…”
Section: Discussionmentioning
confidence: 99%
“…Blots were destained by shaking in 50 mM Tris buffer, pH 7.5, containing 500 mM NaCl and 1% Tween 20. A polyclonal antiserum, specific to the Mip-protein (FKBP25mem from L. pneumophila Philadelphia I), was obtained from rabbit (28).…”
Section: Methodsmentioning
confidence: 99%
“…The genes that encode the 5S and 16S ribosomal subunits have been shown to contain signature sequences that are useful for the identification of L. pneumophila (8,14,15,17,24,28) and a variety of other organisms. More recently, target sequences on these genes have been used in conjunction with real-time PCR for the detection of the Legionella genus, as well as the species L. pneumophila (14,27).The macrophage infectivity potentiator gene, which encodes a 24-kDa protein virulence factor that facilitates the entry of legionellae into amoebae and macrophages, has sufficient sequence variability between the Legionella species to also afford the specific detection of L. pneumophila by PCR (2,6,7,12,13,14,16,21,22,23,25). Although two groups have described real-time PCR assays for the detection of L. pneumophila via detection of the mip gene in water samples, to date only one group has evaluated a real-time PCR for this genetic target for the detection of L. pneumophila in clinical specimens (1,14,28).…”
mentioning
confidence: 99%
“…The macrophage infectivity potentiator gene, which encodes a 24-kDa protein virulence factor that facilitates the entry of legionellae into amoebae and macrophages, has sufficient sequence variability between the Legionella species to also afford the specific detection of L. pneumophila by PCR (2,6,7,12,13,14,16,21,22,23,25). Although two groups have described real-time PCR assays for the detection of L. pneumophila via detection of the mip gene in water samples, to date only one group has evaluated a real-time PCR for this genetic target for the detection of L. pneumophila in clinical specimens (1,14,28).…”
mentioning
confidence: 99%